The Effect of Working Hours on Employee Turnover Intention with Burnout as a Mediating Variable: A Study of the Hospitality Industry in Bandar Lampung - Ranti Rhomantika; Ribhan Ribhan; Lis Andriani HR (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This research examines how working hours affect turnover intention in Bandar Lampung's hotel business and how exhaustion mediates this connection. Hospitality companies have challenges from high turnover intention, which may lower productivity, training expenses, and service quality. The Job Demands-Resources (JD-R) and Conservation of Resources (COR) theories suggest that long hours might lead to burnout, which may make workers want to quit. A cross-sectional survey was used for quantitative research. This survey included 160 staff from three-, four-, and five-star hotels in Bandar Lampung. SEM was used with SmartPLS 4.0 to examine data. The results show that working hours significantly increase turnover intention. Working hours considerably and favorably affect burnout, which positively affects turnover intention. Burnout also strongly mediated the working hours-turnover intention link. Direct influence of working hours on turnover intention was greater than indirect effect via fatigue. Long work hours may lead to employee turnover even without burnout, according to these findings. To prevent employee turnover, hotel management should carefully regulate working hours.